A method for multi-dimensional image segmentation - Hashim, Mazlan (1988)
The main objective of this paper is to assess the crop classification accuracies using the merged TM-MSS data compared to their original data over a selected test site. The study also evaluates the separability of spectral signatures of the studied crops in the selected test site.